Algoritma K-Means dalam Pengelompokan Surat Keluar pada Program Studi Teknik Informatika STMIK Palangkaraya - Rusdiana, Lili; Hardita, Veny Cahya (STMIK Palangkaraya, 2023)
K-Means algorithm as a method of grouping a set of data. The purpose of this study is to find out the use of the K-Means algorithm for outgoing mail data. The method used in this study focuses on the K-Means method. The grouping data used is 284 outgoing mail data at the STMIK Palangkaraya Informatics Engineering Study Program. Outgoing mail data is grouped into two groups, namely staffing and academic administration. Grouping based on letter number, status of recipient of letter, subject of letter. Steps in the K-Means algorithm result two iterations because there is a group movement that occurs, namely there is a movement from one group to another because the value of the object function changes. The iteration can be stopped in 2nd iteration because the object function change value is below the given threshold value, which is 0.1 and there is no group movement in the data used. Two iterations that have occurred, it shows a decrease in the value of changes in object function and data transfer in group locations.